Engaging, Persuading, and Entertaining Citizens: Mediatization and the Australian Political Public Sphere. (January 2015) - Flew, Terry; Swift, Adam
This paper draws upon public sphere theories and the "mediatization of politics" debate to develop a mapping of the Australian political public sphere, with particular reference to television. It discusses the concept of a "political public sphere, " and the contribution of both non-traditional news media genres, such as satirical television and infotainment formats, to an expanded conception of the political public sphere. It considers these questions in the context of two case studies: the Q&A program on the Australian Broadcasting Corporation (ABC), and its uses of social media and interactive formats to engage citizens, and the comedy program Gruen Nation, also on the ABC, which analyzed the use of political advertising to persuade citizens during the 2013 Australian Federal election.